Ba0.5Sr0.5Co0.8Fe0.2O3-δ-based dual-gradient cathodes for solid oxide fuel cells. Issue 4 (March 2018) - Liu, Peng; Luo, Zhifu; Kong, Jiangrong; Yang, Xianfeng; Liu, Qicheng; Xu, He
Abstract: Ba0.5 Sr0.5 Co0.8 Fe0.2 O3- δ (BSCF)/Gd0.2 Ce0.8 O1.9 (GDC) dual-gradient cathodes for solid oxide fuel cells (SOFCs) were prepared via a spraying-sintering route, using corn starch as a pore-forming agent. The X-ray diffraction (XRD) analysis results revealed that the BSCF and GDC showed good chemical compatibility even at 1200 °C. The scanning electron microscopy (SEM) results indicated that a graded pore structure, in addition to a gradient composition, can be obtained by regulating the dosage of the pore-forming agent. Consequently, the dual-gradient cathode possessed a low polarization resistance of 0.25 Ω cm 2 at 750 °C, when the pore-forming agent contents were graded at 5 wt%, 10 wt%, and 15 wt% from the inner sub-layer to the outer sub-layer, respectively. This comparative study indicated that high levels of porosity are beneficial for oxygen transport; however, the variation in the porosity of the adjoining sub-layers should be tailored to guarantee the provision of continuous conductive paths for charge carriers.